On the critical exponent α of the 5D random-field Ising model. (3rd September 2019) - Fytas, N G; Martín-Mayor, Víctor; Parisi, Giorgio; Picco, Marco; Sourlas, Nicolas
Abstract: We present a complementary estimation of the critical exponent of the specific heat of the 5D random-field Ising model from zero-temperature numerical simulations. Our result is consistent with the estimation coming from the modified hyperscaling relation and provides additional evidence in favor of the recently proposed restoration of dimensional reduction in the random-field Ising model at D   =  5.